2014
DOI: 10.1016/j.neuron.2014.04.039
|View full text |Cite
|
Sign up to set email alerts
|

β-Amyloid Inhibits E-S Potentiation through Suppression of Cannabinoid Receptor 1-Dependent Synaptic Disinhibition

Abstract: Summary It has been widely reported that β-amyloid peptide (Aβ) blocks long-term potentiation (LTP) of hippocampal synapses. Here we show evidence that Aβ more potently blocks the potentiation of excitatory post-synaptic potential (EPSP) -spike coupling (E-S potentiation). This occurs not by direct effect on excitatory synapses or postsynaptic neurons, but rather through a novel indirect mechanism: reduction of endocannabinoid-mediated peri-tetanic disinhibition. During high frequency (tetanic) stimulation, so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 79 publications
(136 reference statements)
2
29
0
Order By: Relevance
“…2C). Our findings are consistent with a recent report that synthetic Aβ 42 impairs LTP of PS (Orr et al, 2014), but our naturally secreted human oAβ species (7PA2 CM) and our pure, synthetic Aβ 40 -S26C dimers/oligomers each also blocked fEPSP LTP. There is evidence that hyperactive neurons in cortical circuits of hAPP/PS1 transgenic mice are associated with decreased GABAergic inhibition (Busche et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…2C). Our findings are consistent with a recent report that synthetic Aβ 42 impairs LTP of PS (Orr et al, 2014), but our naturally secreted human oAβ species (7PA2 CM) and our pure, synthetic Aβ 40 -S26C dimers/oligomers each also blocked fEPSP LTP. There is evidence that hyperactive neurons in cortical circuits of hAPP/PS1 transgenic mice are associated with decreased GABAergic inhibition (Busche et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, reducing GABAergic tone favors increased excitability, as some reports have shown that neuronal hyperactivity is associated with decreased GABAergic inhibition, and GABA administration significantly improved cognitive function in APP Tg mice (Busche et al, 2008; Sun et al, 2012). Recent findings also suggest that Aβ-mediated synaptic suppression occurs in part through inhibition of the GABA A receptor (Orr et al, 2014). These results suggest that oAβ can interrupt glutamate uptake, increase extracellular glutamate levels and thereby activate extrasynaptic GluN2B receptors, and can also reduce GABA A receptor-mediated inhibition, thus promoting neuronal hyperexcitability.…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that natural cannabinoids alter the imbalance of excitatory versus inhibitory neural activity in the somatosensory cortex of aged A␤PP/PS1 mice [24,25]. In fact, A␤ has been demonstrated to inhibit long-term plasticity processes associated with learning and memory through suppression of CB 1 -dependent GABAergic synaptic disinhibition [26]. Moreover, CB 1 receptor activity in GABAergic neurons protects against agedependent cognitive decline [27].…”
Section: Discussionmentioning
confidence: 95%
“…In addition, eCB-iLTD is involved the potentiation of excitatory postsynaptic potential (EPSP)-spike coupling (E-S coupling) (Chevaleyre and Castillo, 2003). Intriguingly, exogenous application of β–amyloid peptide (Aβ 1–42 ), whose accumulation occurs in Alzheimer’s disease, prevents eCB-mediated disinhibition and subsequent ES coupling potentiation presumably by interfering with CB 1 signaling (Orr et al, 2014). Although the downstream targets remain to be elucidated, this action of Aβ on eCB signaling represents a mechanism that could underlie the cognitive decline in Alzheimer’s disease.…”
Section: Ecb Signaling At Hippocampal and Neocortical Synapsesmentioning
confidence: 99%